HEPATITIS DELTA VIRUS INFECTION IN MONGOLIA: ANALYSES OF GEOGRAPHIC DISTRIBUTION, RISK FACTORS, AND DISEASE SEVERITY - DAVAALKHAM, DAMBADARJAA; OJIMA, TOSHIYUKI; UEHARA, RITEI; WATANABE, MAKOTO; OKI, IZUMI; NYMADAWA, PAGVAJAV; TAKAHASHI, MASAHARU; OKAMOTO, HIROAKI; NAKAMURA, YOSIKAZU (The American journal of tropical medicine and hygiene, 2006)
The prevalence and risk factors for hepatitis delta virus (HDV) infection among Mongolian school children were assessed by detecting the antibody against HDV and HDV RNA, and through structured interviews. The study subjects consisted of 181 children with the past or ongoing hepatitis B virus infection who were investigated during the nationwide serosurvey conducted in 2004. The prevalence of antibody to HDV was 6.1%, with the proportion of 13.6% among hepatitis B surface antigen (HBsAg)-positive subjects, all of whom had HDV RNA. Multivariate logistic regression analyses showed that injections (> 11 times) (odds ratio [OR] = 8.31, 95% confidence interval [CI] = 1.28–54.07) and blood sampling (> 3 times) (OR = 5.34, 95% CI = 1.12–25.53) in health care settings, hospitalization (> 3 times) (OR = 6.20, 95% CI = 1.18–32.71), and cohabitating with patients with chronic hepatitis (OR = 4.57, 95% CI = 1.26–16.55) predicted the seropositivity for antibody to HDV. These results suggest that parenteral exposures in health care settings and household transmission are the main routes of HDV transmission among Mongolian children.